Dynamic and Thermodynamic Properties of a CA Engine with Non-Instantaneous Adiabats - Ricardo T. Paéz-Hernández; Norma Sánchez-Salas; Juan C. Chimal-Eguía; Delfino Ladino-Luna (Entropy, 2017)
This paper presents an analysis of a Curzon and Alhborn thermal engine model where both internal irreversibilities and non-instantaneous adiabatic branches are considered, operating with maximum ecological function and maximum power output regimes. Its thermodynamic properties are shown, and an analysis of its local dynamic stability is performed. The results derived are compared throughout the work with the results obtained previously for a case in which the adiabatic branches were assumed as instantaneous. The results indicate a better performance for thermodynamic properties in the model with instantaneous adiabatic branches, whereas there is an improvement in robustness in the case where non-instantaneous adiabatic branches are considered.